Clinical governance in primary care groups: the feasibility of deriving evidence-based performance indicators. Issue 2 (1st June 2000) - McColl, Alastair; Roderick, Paul; Wilkinson, Emma; Gabbay, John; Smith, Helen; Moore, Michael; Exworthy, Mark
Abstract : Objectives —To test the feasibility of deriving comparative indicators in all the practices within a primary care group. Design —A retrospective audit using practice computer systems and random note review. Setting —A primary care group in southern England. Subjects —All 18 general practices in a primary care group. Main outcome measures —Twenty six evidence-based process indicators including aspirin therapy in high risk patients, detection and control of hypertension, smoking cessation advice, treatment of heart failure, raised cholesterol levels in those with established cardiovascular disease, and the treatment of atrial fibrillation. Feasibility was tested by examining whether it was possible to derive these indicators in all the practices; the problems and constraints incurred when collecting data; the variations in indicator values between practices in both their identification of diseases and in the uptake of various interventions; the possible reasons for these variations; and the cost of generating such indicators. Results —It was possible to derive eight indicators in all practices and in three practices all 26 indicators. The median number of indicators derived was 12 with two practices able to generate eight. There was considerable variation in the use of computers between practices and in the ability and ease of various practice computer systems to generate indicators. Practices varied greatly in the identification of diseases and in the uptake of effective interventions. Variation in identification of ischaemic heart disease could not be explained by a higher prevalence in practices with a more deprived population. The cost of generating these indicators was £5300. Conclusion —Comparative evidence-based indicators, used as part of clinical governance in primary care groups, could have the potential to turn evidence into everyday practice, to improve the quality of patient care, and to have an impact on the population's health. However, to derive such indicators and to be able to make meaningful comparisons primary care groups need greater conformity and compatibility of computer systems, improved computer skills for practice staff, and appropriate funding. ( Quality in Health Care 2000;9: 90–97)